DISPENSASI PERNIKAHAN DALAM PRESPEKTIF HUKUM POSITIF DI INDONESIA - Kusumawardana, Haris; Hariadi, Wahyu; Iskatrinah, Iskatrinah (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
According to the Explanation of Article 7 paragraph (2) of the Marriage Age Change Law, what is meant by "deviation" is that it can only be done by submitting a dispensation application by the parents of one or both parties of the prospective bride and groom to the Religious Court for those who are Muslim and the District Court for others, if the man and woman are under 19 (nineteen) years old. What is meant by very urgent reasons is "there is no other choice and it is very necessary to have a marriage. What is meant by sufficient supporting evidence", a certificate proving that the age of the bride and groom is still below the provisions of the law and a certificate from a health worker supporting the statement of the parents that the marriage is very urgent to be carried out. The community service carried out aims to increase awareness of carrying out marriages in accordance with positive law in Indonesia and to provide insight to the people of Bendogarap Village about the meaning of marriage dispensation.